Learning Outcomes in Science Using the STEAM Education Approach for Students in Mathayom 2 - Akadecho, Pattarikan (Chophayom Journal, 2026)
This research consists purposes were 1. to develop science lesson plans based on the STEAM Education approach on the topic of Forces in Everyday Life for Students in Mathayom 2 2. to compare the science learning achievement for Students in Mathayom 2 before and after learning through the STEAM Education approach 3. to examine students’ competency in innovation creation in science learning on the topic of Forces in Everyday Life through the STEAM Education approach and 4. to examine students’ satisfaction with science learning through the STEAM Education approach. This study employed a quasi-experimental quantitative research design. The research instruments consisted of lesson plans, a lesson plan appropriateness assessment form, a science learning achievement test, an innovation creation competency assessment form and a satisfaction questionnaire. The sample comprised 20 students in Mathayom 2, who were selected using cluster random sampling, with the school serving as the sampling unit. The data collected from the research instruments were analyzed using descriptive statistics, including percentage, mean and standard deviation and comparisons were conducted using the t-test. The results revealed that 1) the developed lesson plans were rated at the highest level of appropriateness overall (x̅= 4.61, S.D. = 0.49) 2) the students’ science learning achievement after the intervention was significantly higher than that before the intervention at the .05 level 3) the students’ competency in innovation creation was at a high level (x̅= 4.04, S.D. = 0.71) and 4) the students’ overall satisfaction with the STEAM Education approach was at the highest level (x̅= 4.51, S.D. = 0.56).